Understanding the concept of π numbers for elementary school pre-service teachers on circle materials - Dyah Worowirastri Ekowati; Beti Istanti Suwandayani (Jurnal Prima Edukasia, 2020)
This research aims to describe the understanding of the concept of π numbers for elementary school pre-service teachers on circle materials. The research was conducted qualitatively and the type of research conducted was descriptive. The instruments used in this research were observation, interviews, and documentation. The research subjects involved were 45 elementary school pre-service teachers. The results of the research showed that understanding the concept of π numbers for elementary school pre-service teachers had the advantage of classifying objects based on whether or not the requirements that form the concept are fulfilled, identifying the characteristics of operations or concepts and developing the important requirements and/or sufficient requirements of a concept. On the other hand, understanding the concept of π numbers for elementary school pre-service teachers had weaknesses in indicators when applying the concept logically, giving examples or not examples of concepts learned, presenting concepts in various forms of mathematical representation (tables, graphs, diagrams, drawings, sketches, mathematical models, or others) and linking various concepts in Mathematics and out of Mathematics.